A flexible, sandwiched high-performance super-insulation fabric1. Issue 25 (7th July 2015) - Bai, Fan; Wu, Juntao; Gong, Guangming; Guo, Lin
<x xml:space="preserve">Abstract</x> A flexible, sandwiched high-performance super-insulation polyimide fabric has been designed and fabricated. The sandwiched fabric possesses ultra-low thermal conductivity (16.7 mW m−1 K−1), excellent mechanical properties and a wide operating temperature range. The sandwiched fabric will have potential applications under some harsh conditions.